Influence of foliar fertilization with amino acid preparations on morphological traits and seed yield of timothy - Adam RADKOWSKI; Iwona RADKOWSKA (Plant, Soil and Environment, 2018)
The aim of the study was to determine the influence of amino acid fertilizer on yielding ability, morphological characteristics and chlorophyll index of timothy cv. Owacja grown for seed. The experiment was conducted in 2015-2017 at the Experimental Station in Prusy near Krakow, which belongs to the Institute of Plant Production of the University of Agriculture in Krakow. The field trial was set up as a randomized block design with four replications. The soil in the experimental field was a degraded chernozem formed from loess. The plots were sprayed with three doses of Microfert amino acid fertilizer: 1.8, 3.0 and 4.5 L/ha. The highest application rate of foliar fertilization with amino acids (4.5 L/ha) caused a significant (P ≤ 0.05) increase in seed yield and germination capacity compared with the control plot. Successive years of use also had a significant effect on timothy seed yield, which was the highest during the first year of the study. Morphological characteristics were found to improve (taller and longer inflorescences and leaf blades). Satisfactory results (seed yield higher by about 11% to the control plot) were also obtained on the plots where the fertilizer was applied at the rate of 3.0 L/ha.